2021
DOI: 10.1080/21505594.2020.1870834
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 mediates blood-brain barrier permeability and disease in C3H mice during Venezuelan equine encephalitis virus infection

Abstract: Venezuelan equine encephalitis virus (VEEV) is an encephalitic alphavirus that can cause debilitating, acute febrile illness and potentially result in encephalitis. Currently, there are no FDA-licensed vaccines or specific therapeutics for VEEV. Previous studies have demonstrated that VEEV infection results in increased blood-brain barrier (BBB) permeability that is mediated by matrix metalloproteinases (MMPs). Furthermore, after subarachnoid hemorrhage in mice, MMP-9 is upregulated in the brain and mediates B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Furthermore, TLR4 activation, aberrant TLR4 signaling, and hyperinflammation may be to blame for SARS‐CoV‐2‐induced myocarditis and multiple organ injury in COVID‐19 patients. In addition, the study conducted by Hollidge et al (2021) revealed that TLR4 plays a crucial role in modulating the permeability of the BBB and the pathogenesis of encephalitis in C3H mice following infection with the Venezuelan equine encephalitis virus TC‐83 (Hollidge et al, 2021). According to the study, TLR4 has been identified as a promising candidate for the advancement of therapeutic interventions for Venezuelan equine encephalitis virus.…”
Section: Effects Of Covid‐19‐induced Immune Response On the Bbbmentioning
confidence: 99%
“…Furthermore, TLR4 activation, aberrant TLR4 signaling, and hyperinflammation may be to blame for SARS‐CoV‐2‐induced myocarditis and multiple organ injury in COVID‐19 patients. In addition, the study conducted by Hollidge et al (2021) revealed that TLR4 plays a crucial role in modulating the permeability of the BBB and the pathogenesis of encephalitis in C3H mice following infection with the Venezuelan equine encephalitis virus TC‐83 (Hollidge et al, 2021). According to the study, TLR4 has been identified as a promising candidate for the advancement of therapeutic interventions for Venezuelan equine encephalitis virus.…”
Section: Effects Of Covid‐19‐induced Immune Response On the Bbbmentioning
confidence: 99%
“…The TLR2/4 is expressed in the choroid plexus and circumventricular organs [ 45 ]. Equine encephalitis virus interacts with TLR4 and disrupt BBB permeability [ 46 ]. It is tempting to think that SARS-CoV-2 can also interact with these receptors.…”
Section: Evolution Of Covid-19 Symptoms: Outlinedmentioning
confidence: 99%
“…VEEV and EEEV are also highly stable and retain infectivity as aerosols, which greatly increases the possibility of encephalitic disease in infected individuals. VEEV or EEEV exposures due to deliberate aerosol dissemination pose encephalitis concerns because of their ability to establish a quick infection in the central nervous system (CNS) through the olfactory neuron, by-passing the blood–brain barrier (BBB) [ 10 , 11 , 12 , 13 , 14 ]. The establishment of a robust productive infection in the CNS triggers a strong inflammatory response that impacts the integrity of the BBB and contributes to encephalitic disease [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%